Enhancing Knowledge Management Capabilities to Support Business Competitiveness in a Maritime Company - Utama, Armand A. Putra; Hendarman, Achmad Fajar (Graduate Program Magister Manajemen Pendidikan, 2025)
This study expands the maturity level of Knowledge Management (KM) at PT ADK and identifies challenges and strategic solutions to improve its implementation. A quantitative survey of 53 employees and qualitative interviews indicate that PT ADK is at the Initiation stage based on the APO KM framework, with the Technology element scoring the highest. Using the Analytical Hierarchy Process (AHP), the improvement priorities are Technology, Process, and Leadership. Key barriers include fragmented knowledge infrastructure, reliance on individuals, and lack of leadership alignment. To address these, two initiative strategies are proposed: developing integrated knowledge systems and procedures, and fostering a culture of knowledge sharing and continuous learning. These initiatives are expected to improve KM effectiveness, align organizational capabilities with competitive demands, and contribute to business sustainability performance. The study also highlights the long-term potential of KM in driving innovation, preserving institutional knowledge, and increasing employee engagement. The combination of the APO and AHP frameworks offers a structured approach for maritime sector companies seeking to strengthen KM.